Happiness! I passed the entrance exam, but the college is private: Paradoxes of Brazilian higher education - Annor da Silva Junior; Priscilla de Oliveria Martins-Silva; Katia Cyrlene de Araújo Vasconcelos; Vitor Correa da Silva; Mariana Ramos de Melo (Arizona State University, 2017)
Inspired by Martinho da Vila's classic samba, this theoretical essay discusses paradoxes of Brazilian higher education. For this, we traced the evolution of higher education from the colonial period to the present. Based on this evolution, we identified the following paradoxes: the boundary between public and private; the role and characteristics of Higher Education Institutions (HEI), in terms of the tax regime, disclosure and accountability to society; and finally, the role of higher education and its influence on the processes of social inclusion and/or social exclusion for two of the main involved social actors: students and teachers. The central point of the higher education paradoxes seems to be the concept of education as a public good and social right and experienced practice of education as a commodity. The analysis of the paradoxes of Brazilian higher education refers to the understanding that education does not effectively fulfill its role in social inclusion of students and teachers, and, to the contrary, acts as a mechanism of social exclusion. Thus, it is relevant to rethink higher education as a way to solve these paradoxes and facilitate the formation of "petty bourgeois" instead of "poor fellow".